Peer-to-Peer Decentralized Social Media Platform Using Second-Layer Blockchain Technology - Lamonica, Tristan (Université d'Ottawa / University of Ottawa, 2020)
Current social media platforms built on specialized blockchains exist, but have failed to reach mainstream adoption. These decentralized alternatives have not been able to successfully migrate users from the existing offering of centralized platforms due in part to their decisions to create their own specialized currency and blockchain. This study proposes the idea of an algorithmically decentralized social media platform running via a second-layer extension of the blockchain as a solution that would alleviate the failures of previous blockchain iterations, and return social media to a peer-to-peer platform open to everyone as a way to dissipate knowledge, and provide services regardless of political constraints, borders, or personal beliefs. By analyzing this new technology, this thesis explores the opportunities and advantages that second-layer blockchain protocol solutions provide to address the vital concerns, and criticisms of the current internet while addressing which group of users are more likely to understand and favor them. Tweets were extracted and analyzed, finding that individuals are increasingly becoming interested in Bitcoin and second-layer technologies rather than dedicated and segregated projects that have been decreasing in online popularity. The study’s geographic, historical, and economic analysis suggests that in order for decentralized social media platforms to stay truly decentralized and to reach mainstream adoption, they will need to integrate with the Bitcoin blockchain to build on the already established momentum. The second-layer solution being proposed by this study solves technological complications and increases the likelihood of mainstream adoption.
Keywords: Communication; Bitcoin; Blockchain; Decentralized; Peer-to-peer; Social media; Algorithms